2015
DOI: 10.1186/s12989-015-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of gold nanoparticles across the lung epithelial tissue barrier: Combining in vitro and in silico methods to substitute in vivo experiments

Abstract: BackgroundThe lung epithelial tissue barrier represents the main portal for entry of inhaled nanoparticles (NPs) into the systemic circulation. Thus great efforts are currently being made to determine adverse health effects associated with inhalation of NPs. However, to date very little is known about factors that determine the pulmonary translocation of NPs and their subsequent distribution to secondary organs.MethodsA novel two-step approach to assess the biokinetics of inhaled NPs is presented. In a first s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 75 publications
(135 reference statements)
7
74
0
Order By: Relevance
“…Translocation of Au NPs in sizes between 2 and 80 nm across human and murine alveolar cell monolayers was similar to in vivo data and ranged between 0.2 and 2 % of the applied particles (Bachler et al 2015). Translocation was inversely related to particle size and constant up to 100 ng/cm 2 .…”
Section: Respiratory Routesupporting
confidence: 51%
“…Translocation of Au NPs in sizes between 2 and 80 nm across human and murine alveolar cell monolayers was similar to in vivo data and ranged between 0.2 and 2 % of the applied particles (Bachler et al 2015). Translocation was inversely related to particle size and constant up to 100 ng/cm 2 .…”
Section: Respiratory Routesupporting
confidence: 51%
“…This estimate is consistent with those derived from pulmonary instillation of particles in animal models, 33,34 and those derived from in vitro – in silico modeling. 35 The majority of inhaled nanoparticles are retained in the alveolar region and are slowly cleared over time. 25 In the present study, gold was still detectable in blood and urine at 3 months, consistent with ongoing translocation of gold either through the alveolar membrane or possibly via the gastrointestinal tract after clearance by the mucociliary escalator.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Wagner et al observed that in vitro PEI/DNA particles that are formed by simple pipetting at low N/P ratios tend to aggregate and increase in overall size which, in turn, leads to more efficient gene knockdown of the aggregated particles in vitro due to differences in sedimentation rates [24]. However, in vivo sedimentation plays a secondary role, and larger particles are phagocytosed and cleared by macrophages more rapidly, while smaller particles more efficiently diffuse through mucus and surfactant in the lung and are more efficiently endocytosed by the epithelium [39]. Additionally, another possible explanation for the increase in gene efficiency lies in the possibilty for our particles to undergo transcytosis.…”
Section: Resultsmentioning
confidence: 99%